2009
DOI: 10.1111/j.1651-2227.2008.01082.x
|View full text |Cite
|
Sign up to set email alerts
|

Reducing blood transfusion requirements in preterm infants by a new device: a pilot study

Abstract: The use of ErythroSave for sampling blood significantly reduced blood transfusion requirements in premature infants compared to sampling by conventional syringes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…In recent years, technological advances have led to an increasing range of analytes measurable using microsample point‐of‐care platforms. ‘In‐line’ umbilical arterial catheter devices are now available to perform blood gas, Hct and electrolyte analysis without removing any blood from the infants (Widness et al , ; Ballin et al , ). For laboratory‐based tests, the use of placental blood for routine admission tests (such as blood culture, haematological and biochemical baseline status), the introduction of neonatal sampling tubes with clearly marked minimum volumes, and the return to the infant of deadspace blood draws via arterial catheters have significant reduced iatrogenic blood loss (Carroll & Widness, ).…”
Section: Preventive Strategies For Anaemia Of Prematuritymentioning
confidence: 99%
“…In recent years, technological advances have led to an increasing range of analytes measurable using microsample point‐of‐care platforms. ‘In‐line’ umbilical arterial catheter devices are now available to perform blood gas, Hct and electrolyte analysis without removing any blood from the infants (Widness et al , ; Ballin et al , ). For laboratory‐based tests, the use of placental blood for routine admission tests (such as blood culture, haematological and biochemical baseline status), the introduction of neonatal sampling tubes with clearly marked minimum volumes, and the return to the infant of deadspace blood draws via arterial catheters have significant reduced iatrogenic blood loss (Carroll & Widness, ).…”
Section: Preventive Strategies For Anaemia Of Prematuritymentioning
confidence: 99%
“…Only two studies observed a significant decrease in transfusion number in the intervention group (30, 33). One similar study in neonates observed a significantly lower transfusion volume when returning hemodiluted discarded blood with the ErythroSave device (ErythroSave, Tel Aviv, Israel) (a disposable sterile syringe which avoids the blood to cloth) (36).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies reported other health-related outcomes and showed no increase in adverse events such as sepsis or mortality and similar or shorter lengths of ICU and hospital stay (29, 30, 32–34, 36, 41, 44, 48, 49, 57). We were unable to evaluate the effect of quality improvement interventions on costs or other outcomes in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that minimizing blood wasting should be an important intervention to introduce into clinical practice. Blood conservation devices can help to reduce the amount of blood wasted for line rinsing (21,(28)(29)(30)(31)(32)(33). Arterial closed blood sampling devices such as the Venous-Arterial blood Management Protection device can significantly lower the amount of blood volume discarded (28)(29)(30)34).…”
Section: Discussionmentioning
confidence: 99%
“…Arterial closed blood sampling devices such as the Venous-Arterial blood Management Protection device can significantly lower the amount of blood volume discarded (28–30, 34). Returning hemodiluted discarded blood with the ErythroSave device (a disposable sterile syringe that avoids the blood to cloth) has also been shown to significantly lower transfusion requirements in neonates (33). Small volume tubes, as used in our unit, and bedside point-of-care tests may reduce the blood volume required for testing, especially for coagulation testing that generally requires more blood volume than other tests (35).…”
Section: Discussionmentioning
confidence: 99%